Construcción de un módulo de control en cascada de nivel para el laboratorio de Ingeniería Electromecánica de la Universidad Técnica de Cotopaxi”. - Quinatoa Quinatoa, Wilmer Adrián (2020)
"The objective of this degree work was to control the level cascade through level and flow transmitters and a visualization on an HMI screen for the analysis of a simple loop PID controller with a cascade PID, the comparisons were made in the module that was developed and is located in the Laboratory of the Electromechanical Engineering Career of the Technical University of Cotopaxi It was theoretically supported by [2], [3], [4], [5] The methodology is classified into bibliographic research, field research and experimental research. The investigation was composed of three phases: observation of the behavior of the analog instruments, measurement of the data collection of the real values of the level transmitters, validation flow of the level cascade control module through experimental tests to compare the loop PID controller simple with a cascading PID. The results show that the flow behaves as a second order process while the level as a first order, which were tuned using the Lambda methods for flow and Rovira for level, the proportional, integral and derivative gains in cascade managed to stabilize the value. measured level within the margin of error of 2% in the comparison between the Ziegler-Nichols, Lambda and Rovira methods, the result is that the best tuning method for the level signal is Rovira with a stability time of 32.9s and for the flux signal tuning it is Lambda with a stability time of 39.75s. and the stability time of the simple loop PID for level is 32.9s for flow is 39.7s compared to a cascade PID which is much faster with a time for level of 1.1s and for flow of 2, 1s thus resulting when a disturbance will stabilize faster.